2017
DOI: 10.1002/14651858.cd011741.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors for angiogenesis in peripheral arterial disease

Abstract: The results of this review do not support the use of therapy with the growth factors FGF, HGF or VEGF in people with PAD of the lower extremities to prevent death or major limb amputation or to improve walking ability. However, the use of these growth factors may improve haemodynamic measures and decrease the rate of any limb amputations (probably due to preventing minor amputations) with an uncertain effect on adverse events; an improvement of ulceration and rest pain is very uncertain. New trials at low risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 73 publications
0
22
0
1
Order By: Relevance
“…Local interventions reducing wound pain included one study each on ibuprofen‐containing wound dressings, or a growth factor construct or two studies applying topical anaesthetic cream before ulcer debridement …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Local interventions reducing wound pain included one study each on ibuprofen‐containing wound dressings, or a growth factor construct or two studies applying topical anaesthetic cream before ulcer debridement …”
Section: Resultsmentioning
confidence: 99%
“…Most (14 controlled studies on 389 patients) reported healing outcomes for those with severe PAD. Systematic reviews have reported that three RCTs each supported faster or earlier complete healing of ischaemic ulcers on patients with ABI > 0.5 managed with autologous stem cell therapy or angiogenic growth factors . Two studies each supported improved ulcer healing in patients with severe PAD receiving lower leg IPC or spinal cord stimulation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymer nanoparticles such as poly(lactic‐ co ‐glycolic acid) nanoparticles (PLGA NPs) have also been used for targeted delivery of therapeutic agents, including genes to ischemic sites in peripheral arteries to overcome safety issues of viral vectors for gene delivery . The VEGF cDNA loaded NPs promoted significant angiogenesis with dense capillaries, improved collateral circulation, and improved expression of the VEGF gene in rabbit ischemic models when compared to that of naked plasmid administration .…”
Section: Application Of Nanoparticles For the Treatment Of Padmentioning
confidence: 99%